INTERNALIZATION OF SPIRITUAL INTELLIGENCE VALUES THROUGH THE STUDY OF THE BOOK ARBAIN AN-NAWAWI AMONG STUDENTS AT MA’HAD AL-JAMI’AH, RADEN FATAH STATE ISLAMIC UNIVERSITY, PALEMBANG - Amirul Haqi; Ris'an Rusli; Ismail Sukardi (LP2M IAI Al-Khairat Pamekasan, 2026)
The aim of this research is to determine the process of internalizing Islamic spiritual intelligence values ​​through the study of the Hadith book Arba'in An-Nawawi. So that students can analyze and evaluate indicators of achievement of both supporting and inhibiting factors in the internalization of spiritual intelligence. Internalization is an effort made by educators to produce students by developing high spiritual intelligence. Spirituality in question includes faith, character (characterization), morals, faith, Islam, ihsan. However, in reality the values ​​that are internalized to obtain spiritual competence have not been able to change the character of mahasantri as a whole. This research was carried out at Ma'had Al-Jami'ah, Raden Fatah State Islamic University, Palembang, which was the object of research and made Mr Mudir, teacher of the Arba'in Hadith book and Mahasantri as the subject of this research. The result of internalizing this is so that it can be integrated into the value of ukhuwwah, such as goodness that is rooted in the mahasantri individual. This research used a descriptive qualitative method conducted at Ma'had Al-Jami'ah, Raden Fatah State Islamic University, Palembang. The data collection techniques are observation, interviews and documentation. In conclusion, fulfilling the spiritual intelligence that has been taught through the study of the Hadith book Arba'in An-Nawawi has a positive impact on many things, one of which is regarding the faith and piety of mahasantri.